Current Therapeutic Strategies in BRAF-Mutant Metastatic Colorectal Cancer - Grassi, Elisa; Corbelli, Jody; Papiani, Giorgio; Barbera, Maria Aurelia; Gazzaneo, Federica; Tamberi, Stefano (Frontiers in Oncology, 2021)
About 8-12% of advanced colon rectal cancer (CRC) presents BRAF alteration, particularly V600E mutation, which is associated with right-side, poorly differentiated and mucinous type tumor. The presence of BRAF mutation (BRAF-mt) has been identified as hallmark of worse prognosis and the optimization of therapeutic strategy in this subgroup of patients is an important goal. Currently the standard of care is an aggressive strategy involving triplet chemotherapy and anti-VEGF agents, but new therapeutic approaches are emerging. Particularly promising results have been obtained by target therapies combination, such as anti-BRAF agents plus anti- EGFR agents. Furthermore BRAF-mt patients present a strongly association with high microsatellites instability (MSI-H), observed in about 60% of cases and the immune checkpoint inhibitors could represent the new standard of care for this subgroup. . The focus of this review is summarizing the current strategies for BRAF mutant CRC treatment, highlighting the new therapeutic options.